Structural and ultrastructure changes show an increase in amoeboid forms in Heterosigma akashiwo (Raphidophyceae), during recovery after nutrient depletion. (2nd November 2017) - Papini, A.; Fani, F.; Belli, M.; Niccolai, C.; Tani, C.; Di Falco, P.; Nuccio, C.; Lazzara, L.
Abstract: Heterosigma akashiwo shows remarkable ultrastructural changes during the recovery from a late stationary phase ("aged" culture) induced by nutrient depletion. H. akashiwo cells showed different morphological types in "aged" cultures, with an increase in irregular cells and cell fragments. The irregular cells mostly corresponded to an amoeboid shape of the cell. Many of these cells showed chloroplasts with a homogeneous matrix of medium electron density lacking most thylakoids and condensed nucleus, probably as a result of cyst/resting cells germination. In other cells, we observed nuclear blebbing without chromatin condensation and changes in mitochondrion ultrastructure. Some vegetative cells in active phase ("young" culture) were connected to each other, apparently phagocytizing cytoplasmic fragments and intact chloroplasts in the medium. An explanation for the phenomenon may reside in the need of acquiring organic material after nutrient reduction for a faster recovery. On the basis of our observations, we conclude that some ultrastructural features, normally used to distinguish between different species and strains of Raphidophyceae, may be related to different physiological states and should be used with caution for systematic purposes.